Factors Influencing Decision Making in the Regional House of Representatives - Muh. Said; Mustaking Mustaking (PINISI Discretion Review, 2021)
This study aims to determine the factors that influence decision making. The location of the research was carried out in the office of the agency for the formation of regional regulations, Regional House of Representatives (Indonesia: Dewan Perwakilan Rakyat Daerah / DPRD) of Takalar district. The sample used in this study were members of the DPRD of Takalar Regency with a sample of 52 people, the research method used in this study was the quantitative method. The results of this study prove that, 1) there is a significant positive influence between knowledge management with decision making, 2) There is a significant positive influence between Learning Organization and decision making, and 3) There is a positive and significant influence on talent management with decision making.